Concurrent Systemic Chemoimmunotherapy and Sofosbuvir-Based Antiviral Treatment in a Hepatitis C Virus-Infected Patient With Diffuse Large B-Cell Lymphoma. (20th December 2016) - Ewers, Evan C.; Shah, Phalgoon A.; Carmichael, Mark G.; Ferguson, Tomas M.
Abstract: Hepatitis C virus (HCV) infection is associated with the development of non-Hodgkin lymphomas. For aggressive lymphomas, such as diffuse large B-cell lymphoma (DLBCL), treatment of HCV infection is typically deferred in treatment-naive patients until after completion of lymphoma therapy [1, 2] . We report a case of HCV-associated stage IV DLBCL successfully treated concurrently using chemoimmunotherapy and a sofosbuvir-based antiviral regimen.